ADOLESCENT KNOWLEDGE ABOUT BREAST CANCER DETECTION THROUGH D3 NURSING SIDOARJO - Putri Romadloni; Loetfia Dwi Rahariyani (Global Ten Public Health and Nursing Journal, 2024)
Currently, many young women suffer from breast cancer, due to not doing early detection of breast cancer by breast self-examination (BSE). BSE is an early detection effort to find lumps or abnormalities in the breast. This study used a descriptive research design with a sample of 178 respondents using a total sampling technique. The questionnaire used for data collection is in digital form using Google forms with reference to specific objectives consisting of knowledge, sources of information and implementation of BSE. Based on the results of the study, it was shown that the majority of young women's knowledge about early detection of breast cancer through breast self-examination (BSE) was sufficient (65.2%). The majority of knowledge is based on information sources from 110 people and most of them get information from electronic media. Most of the 86 people who had performed BSE had done it once. Seeing the results of this study, it is hoped that D3 Nursing students will know the importance of doing BSE correctly. Because breast self-examination (BSE) is very important for the D3 Nursing Study Program in Sidoarjo because they are studying in the health sector who will become potential health educators and educators who will later go into the community